(untitled) (Journal of the College of Basic Education, 2025)
This study aimed to identify the effect of using the inquiry strategy on the motivation of first-stage students in the Physics Department at the College of Education/Al-Mustansiriyah University towards learning the subject of practical mechanics. The researcher adopted the experimental approach, and the research sample included all students of the aforementioned stage in its morning study, totaling 144 students, who were divided into two equal groups, the first experimental group in which they study according to the inquiry strategy and the second control group that studies according to the usual method. The research requirements were prepared, represented by a scale to measure learning motivation towards the subject of scientific mechanics. After the researcher verified the validity and reliability of the scale paragraphs, it was prepared in a final form of 35 paragraphs. When conducting the experiment, it was found that there were statistically significant differences at the level (0.05) between the averages of the motivation of the control and experimental groups, in favor of the experimental group that studied using the inquiry strategy. In light of these results, a set of recommendations and proposals were developed to complete the scientific research process.